Pemanfaatan Media Sosial dalam Memperbaiki Reputasi Content Creator Tiktok “Willie Salim” - Erika Yosita Putri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research provides an overview to find out how the utilization of social media, especially TikTok in increasing the reputation of content creator Willie Salim. TikTok is the most superior social media today compared to other social media. TikTok is an application that is widely used among the younger generation because TikTok provides a lot of entertainment and opportunities to build and improve their reputation. Reputation is an important asset that content creators must have, especially Willie Salim because if their reputation is good it can attract followers and attract cooperation and vice versa, a negative reputation can greatly hinder a content creator's career. The purpose of this research is to understand how Willie Salim handles reputation-related issues through strategic responses to crises and managing public perception. Using a qualitative approach, this research explores Willie Salim's experiences and strategies in utilizing TikTok and other social media platforms. Based on reputation management theory, this research focuses on how important public image management is, emphasizing the role of performance and communication in building reputation. The researcher wanted to show that Willie Salim actively interacts with his audience through relevant content, which encourages transparency and trust, especially through features such as live streaming. This research provides insights for creators facing similar challenges, emphasizing the need for consistent communication and proactive engagement with audiences to rebuild and maintain a positive reputation in the digital age.